2022
DOI: 10.3390/ijerph191710528
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Predicting the Change in the Cumulative Exposure of New Tobacco and Related Products Based on Emissions and Toxicity Dose–Response Data

Abstract: Many novel tobacco products have been developed in recent years. Although many may emit lower levels of several toxicants, their risk in the long term remains unclear. We previously published a method for the exposure assessment of mixtures that can be used to compare the changes in cumulative exposure to carcinogens among tobacco products. While further developing this method by including more carcinogens or to explore its application to non-cancer endpoints, we encountered a lack of data that are required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Separate authors have, however, concluded that the available datasets in relation to HTPs remain limited and conclusions relating to HTPs should be taken with caution [55]. It is apparent that further research is warranted, and additional epidemiological studies into the long-term effects of HTP use may help to determine the absolute cancer risk associated with HTP use [56].…”
Section: Summary Of Aerosol Chemistry Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Separate authors have, however, concluded that the available datasets in relation to HTPs remain limited and conclusions relating to HTPs should be taken with caution [55]. It is apparent that further research is warranted, and additional epidemiological studies into the long-term effects of HTP use may help to determine the absolute cancer risk associated with HTP use [56].…”
Section: Summary Of Aerosol Chemistry Datamentioning
confidence: 99%
“…With respect to toxicological risk assessments, the available evidence indicates that HTP use may be associated with reduced cancer- and non-cancer-related risk when compared to cigarette smoking [ 52 - 54 ]. Separate authors have, however, concluded that the available datasets in relation to HTPs remain limited and conclusions relating to HTPs should be taken with caution [ 55 ]. It is apparent that further research is warranted, and additional epidemiological studies into the long-term effects of HTP use may help to determine the absolute cancer risk associated with HTP use [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…Dies beinhaltet auch die Untersuchung der (neuen) Aromastoffe in den Einwegtabaksticks sowie deren Wechselwirkungen mit den bekannten Tabakinhaltsstoffen nach Erhitzung auf bis zu 350 °C. Möglicherweise entstehen auch völlig neue chemische Verbindungen [26].…”
Section: Tabakerhitzer (Heat-not-burn-produkte)unclassified